The effect of accountability and professionalism auditor on audit opinion in the office public accountant in Medan City / Maya Sari, Dira Rindani and Eka Nurmala Sari - Sari, Maya; Rindani, Dira; Sari, Eka Nurmala (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
This study aims to determine the effect of accountability and auditor professionalism on audit opinion at the Public Accounting Firm in Medan City. In this study, the sample used was determined using a purposive sampling technique, namely the sampling technique with certain considerations in order to obtain samples that match the specified criteria. The data collection technique used is a questionnaire. Data analysis in this study used outer model analysis, inner model analysis and hypothesis testing using Partial Least Square (PLS) software version 3.3. The results of this study indicate that there is a significant effect of the accountability variable and the professionalism variable on audit opinion at a public accounting firm in Medan City.